Ubiquitination-Related MdBT Scaffold Proteins Target a bHLH Transcription Factor for Iron Homeostasis . Issue 3 (22nd September 2016) - Zhao, Qiang; Ren, Yi-Ran; Wang, Qing-Jie; Wang, Xiao-Fei; You, Chun-Xiang; Hao, Yu-Jin
Abstract : BTB-TAZ proteins bridge and scaffold the CRL3 complex to modulate iron homeostasis by ubiquitinating and degrading MdbHLH104 proteins in response to Fe status in apple. Abstract: Iron (Fe) homeostasis is crucial for plant growth and development. A network of basic helix-loop-helix (bHLH ) transcription factors positively regulates Fe uptake during iron deficiency. However, their up-regulation or overexpression leads to Fe overload and reactive oxygen species generation, thereby damaging the plants. Here, we found that two BTB/TAZ proteins, MdBT1 and MdBT2, interact with the MbHLH104 protein in apple. In addition, the function of MdBT2 was characterized as a regulator of MdbHLH104 degradation via ubiquitination and the 26S proteasome pathway, thereby controlling the activity of plasma membrane H + -ATPases and the acquisition of iron. Furthermore, MdBT2 interacted with MdCUL3 proteins, which were required for the MdBT2-mediated ubiquitination modification of MdbHLH104 and its degradation. In sum, our findings demonstrate that MdBT proteins interact with MdCUL3 to bridge the formation of the MdBTs MdCUL3 complex, which negatively modulates the degradation of the MdbHLH104 protein in response to changes in Fe status to maintain iron homeostasis in plants.